Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Developmental and transgenerational effects of climate change on inorganic mercury toxicity in a marine copepod - Fankang Zhao; Shiru Lin; Jae-Seong Lee; Minghua Wang (Journal of Environmental Sciences, 2026)

Unraveling the Tectonic Evolution of the Eastern Jiangnan Orogen, South China: Constraints From Basalts of Trace Elements, Nd Isotope, and Geochronology - Jiandong Sun; Xuehui Zhang; Jinsong Lv; Haili Li; Shiru Lin (Island Arc, 2026)
The Jiangnan Orogen has long been recognized as an ideal location for Precambrian geologists to study Neoproterozoic tectonic movements. However, the paleogeographic location of the South China Craton within the Rodinia supercontinent and the associated geodynamic mechanisms remain contentious. This research presents results from Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) zircon U–Pb dating, whole‐rock geochemistry, and Nd isotopes of early Neoproterozoic Jinshan basalts from the Zhangcun Formation. The basalts, dated at approximately 844 Ma, display a tholeiitic affinity, characterized by high MgO (8.19–13.70 wt.%), moderate TiO 2 (0.89–1.40 wt.%), and positive ε Nd ( t ) values (+ 1.35 to +3.53). Normalized rare earth element (REE) patterns and primitive mantle‐normalized trace element distributions indicate a slight enrichment of light rare earth elements (LREE) and a significant enrichment of large ionic lithosphere elements (LILEs), comparable to E2 basalts from the East Scotia Ridge back‐arc basin. It is suggested that the Jinshan basalts originated from a slightly depleted asthenospheric mantle, combined with recycled slab melt. When integrated with existing regional data, these basalts from the eastern Jiangnan Orogen exhibit notable geochemical anomalies, including elevated LREE and incompatible element ratios, as well as lower ε Nd ( t ) values, in contrast to back‐arc basin basalts from the central Jiangnan Orogen. This study proposes that the observed geochemical disparities between the eastern and central Jiangnan Orogen are attributed to varying degrees of slab rollback within the Yangtze Block during the early Neoproterozoic. Furthermore, evidence from prolonged arc magmatism and extensional tectonics related to slab rollback supports the conclusion that the South China Craton is positioned at the periphery of the Rodinia supercontinent.

Multigenerational exposure reveals differential effects of ocean warming temporal scenarios on mercury toxicity in a marine copepod - Luman Cheng; Zhuoan Bai; Shiru Lin; Jae-Seong Lee; Quanlong Li; Minghua Wang (Water Research, 2025)

Multigenerational impact of global change: Increased mercury toxicity in a marine copepod - Shiru Lin; Fankang Zhao; Yao Chen; Minghua Wang (Journal of Hazardous Materials, 2025)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

A new insight into the molecular rearrangement of sulfurized polyacrylonitrile cathode in ether electrolyte - Wei Wang; Wangcong Xu; Shuhang Xia; Wenying Xue; Jin Wang; Xiaofei Wang; Huilan Li; Shiru Lin; Yu Zhao; Lina Wang; Yonggang Wang (Chemical Engineering Journal, 2023)

Coupling and decoupling of Au and As in pyrite from Carlin-type Au deposits, southwest China - Shiru Lin; Kai Hu; Jian Cao; Yin Liu; Shengjun Liu; Bin Zhang (Journal of Asian Earth Sciences, 2023)

An overview of 2D metal sulfides and carbides as Na host materials for Na-ion batteries - Javed Rehman; Shiru Lin; Mehwish K. Butt; Xiaofeng Fan; Tamer Khattab; Khaled A. Elsayed; Mohamed F. Shibl (Chemical Engineering Journal, 2023)

Promising energy-storage applications by flotation of graphite ores: A review - Ye Chen; Shilong Li; Shiru Lin; Mingzhe Chen; Cheng Tang; Xinghui Liu (Chemical Engineering Journal, 2023)